STRATEGI MODERNISASI MILITER INDONESIA DALAM PENYEIMBANGAN KEKUATAN MILITER DENGAN NEGARA-NEGARA DI ASIA TENGGARA TAHUN 2008-2014 - Iskandar, Nanda; ", Pazli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This study identifies Indonesian military modernization strategy inbalancing military power with countries in Southeast Asia 2008-2014. The needfor the Indonesian military modernization is inseparable from some reason. Thechange due to the threat of global development, the increase in the defense budgetin the countries of Southeast Asia which borders with Indonesia, the need to addand rejuvenation Indonesian defense equipment which can be categorized notfeasible. The main objective of the modernization of Indonesia as securitystability in the country and the effects desist threats coming from outside. For thatframework built Minimum Essential Force (MEF) which is an ideal posture interms of resources and defense equipment that must be owned by Indonesia.Keywords: : Modernization of the Indonesian military, The Minimum EssentialForce (MEF)